A biomechanical and physiological study of office seat and tablet device interaction. (July 2017) - Weston, Eric; Le, Peter; Marras, William S.
Abstract: Twenty subjects performed typing tasks on a desktop computer and touch-screen tablet in two chairs for an hour each, and the effects of chair, device, and their interactions on each dependent measure were recorded. Biomechanical measures of muscle force, spinal load, and posture were examined, while discomfort was measured via heart rate variability (HRV) and subjective reports. HRV was sensitive enough to differentiate between chair and device interactions. Biomechanically, a lack of seat back mobility forced individuals to maintain an upright seating posture with increased extensor muscle forces and increased spinal compression. Effects were exacerbated by forward flexion upon interaction with a tablet device or by slouching. Office chairs should be designed with both the human and workplace task in mind and allow for reclined postures to off-load the spine. The degree of recline should be limited, however, to prevent decreased lumbar lordosis resulting from posterior hip rotation in highly reclined postures. Highlights: This study explored biomechanical and discomfort measures in prolonged sitting. Seating design should accommodate the human and the technology used for a task. Heart rate variability can serve as an objective measure of seating discomfort.